Caregivers' hesitancy and outright refusal toward children's COVID-19 vaccination in the Democratic Republic of Congo: A community-based cross-sectional study - Guillaume, Ashuza Shamamba; Ndwandwe, Duduzile; Nyalundja, Arsene Daniel; Bugeme, Patrick Musole; Ntaboba, Alain Balola; Hatu'm, Victoire Urbain; Tamuzi, Jacques Lukenze; Iwu-Jaja, Chinwe; Shindano, Tony Akilimali; Wiysonge, Charles S.; Katoto, Patrick D.M.C. (Human vaccines & immunotherapeutics, 2024)
Data from the global South show higher COVID-19-related mortality in children compared to the North. Parents' willingness to vaccinate their children once COVID-19 vaccines are available is poorly documented. We assessed parents' willingness to vaccinate their children in the DRC. A year after the vaccination program started, we conducted a population and online-based cross-sectional study, using the WHO modified Behavior and Social Drivers questionnaire among parents and caregivers in the eastern DRC. We performed Modified Poisson regressions to determine factors associated with vaccine hesitancy and outright refusal, focusing on the intention to vaccinate one's children as our primary outcome. Of the 1709 respondents aged 38 years, 82.56% were unwilling to vaccinate their children, of which 26.80% were hesitant and 55.76% were outright refusals. Drivers of hesitancy were religious refusal of vaccine, non-healthcare status, and caregiver beliefs about vaccine unsafety. Independent predictors of refusal were religious refusal of vaccine, neither healthcare nor student status and belief about vaccine effectiveness, unsafety, and distrust. In addition, both hesitancy and refusal to vaccinate one's children were driven by not being ready to get vaccinated if recommended or mandated. In contrast, parents' and caregivers' trust in the government and readiness to vaccinate themselves reduced hesitancy and outright refusal to vaccinate one's children, respectively. Briefly, COVID-19 vaccine hesitancy and outright refusal in eastern DRC are influenced by individual (subjective convictions) and system-level factors (government confidence, mandate trust). It is important to address these issues to improve vaccine coverage during disease outbreaks and mitigate public health risks.